Injections from sub-μL sample volumes in commercial capillary electrophoresis - Šlampová, Andrea; Kubáň, Pavel (Journal of chromatography. A, 2017)
A simple sample injection procedure compatible with commercial capillary electrophoresis (CE) instrumentation was developed, which enables handling sample volumes as little as 250nL for analytical applications where sample volume availability is of concern. Single-use micro-sampling inserts were prepared by thermal modification of polypropylene micropipette tips and the inserts were accommodated in standard CE vials in CE autosampler carousel. To ensure direct contact of separation capillary injection end with sample solution and to avoid possible damage to the capillary, a soft compression spring was placed at the bottom of the vial underneath the micro-sampling insert. Injections from sub-μL samples were carried out in conventional as well as in short-end injection mode, were compatible with standard i.d./o.d. (25-100μm/365μm) fused silica capillaries and with various background electrolyte solutions and detection modes. Excellent repeatability of replicate injections from 250nL to 3μL was achieved based on RSD values of quantitative analytical measures (peak heights ≤2.4% and peak areas ≤3.7%) for CE-UV-vis, CE-ESI-MS and CE-contactless conductivity detection of model basic drugs. The achieved RSD values were comparable with those for replicate injections of the drugs from standard CE vials. The reported concept of injections from micro-sampling inserts was further demonstrated useful in evaluation of micro-electromembrane extraction (μ-EME) of model basic drugs. Sub-μL volumes of operational solutions resulted in reduced lengths of μ-EME phases and improved extraction recoveries (66-91%) were achieved.
Keywords: roztoky; Capillary electrophoresis; Electrophoresis, Capillary; Micro-extractions; elektroforéza kapilární; UV–vis detection; elektrolyty; Mass spectrometry; spektrofotometrie ultrafialová; Nortriptyline; hmotnostní spektrometrie; Solutions; Electrolytes; Spectrophotometry, Ultraviolet; Micro-sampling; Mass Spectrometry; Contactless conductivity detection; nortriptylin; papaverin; Papaverine